The Impact of Negative/Positive Emotions on English Language Teachers` Identity: A Qualitative Research - Vida Orouji (UICELL, 2020)
This study was a qualitative research into the impact of emotions on the professional identities of teachers. The researcher follows Zembylas (2005a, 2005b) in conducting this study following the argument that politics and disciplinary power affect every aspect of teachers` lives, hence their emotions and professional identities. Foucault (1975 & 1984) was the source of theoretical underpinning in this study. The researcher used an open written interview and a written narrative inquiry. Ten English language teachers (8 English Institution teachers, 2 public school teachers) took part in the first phase. Finally, six English language teachers participated in the final phase. The study indicated that both groups of teachers have held negative emotions because of institution and governmental rules and positive emotions because of their success and their relationships with their students. English Institution teachers also experience negative emotions because of underpayment. This study implies that politics has its own way even in shaping the way teachers think they should express and suppress their emotions. Politics has penetrated deep enough to tell teachers what to teach, how to teach, and when to show emotions. Hence, teachers` dissatisfaction with institution and school strategies, policies, and rules.